GAMBARAN KECEMASAN SOSIAL PADA REMAJA YANG MENGALAMI BULLYING DI DESA RAGAJAYA - Insyafiatul Aminah, (2021)
Social anxiety is one of the factors that causes adolescents to withdraw from the association due to fear received from others. This study aims to determine the description of social anxiety in adolescents who experience bullying. This type of research is a descriptive survey method. The number of samples of 85 respondents was taken by purposive sampling technique where the respondents were with experience of bullying. The questionnaire used the Liebowitz Social Anxiety Scale (LSAS). The results showed that the average age of 17 years in measuring social anxiety in the age range of 12-20 years in Ragajaya Village consisted of 34.1% men and 65.9% women. There are 45.9% of adolescents who experience high social anxiety. Social anxiety is more experienced by women than men. Research provides basic data that the average adolescent girl experiences social anxiety. For parents, this study is useful in providing a motivating for adolescents who experience bullying so as not not experience social anxiety.